CARIES PREVENTION AS THE MOST IMPORTANT ASPECT OF CHILDREN'S DENTAL HEALTH PRESERVATION - E.M. Kuz'mina; I.I. Lysenkova (Педиатрическая фармакология, 2007)
The authors have studied the efficiency of the vitamin and mineral complex calcinova (KRKA, Slovenia) in the caries prevention. 80 children aged between 7 and 12 years old, with nidi of teeth enamel demineralization took part in the research. All the children received the vitamin and mineral complex (1 pill 3 times day for 3 months). The research findings showed that rational use of the vitamin and mineral complex led to the saliva saturation with minerals, such as: calcium, magnesium and phosphorus. The intake of the vitamin and mineral complex within the period of enamel growth and maturation conduced to the suspension of the further carious process development.Key words: calcium, caries, prevention, children, vitamin and mineral complex.